Práticas de alfabetização em contextos de 1º ano do ensino fundamental : retratos de um cenário escolar público estadual e um municipal - Omitto, Melina Borges (2019)
This research is inserted in the line of Formation, Practical Politics and in Education of the Program of After-Graduation in Education of the School of Humanities of the Pontifical Catholic University of Rio Grande do Sul (PPGEdu / PUCRS). It has been the objective to investigate which practical pedagogical are used and considered the potencializadoras and / or the limiter ones in contexts of alphabetization in 1st year of Basic Teaching in two public schools of the Region Metropolitan of Porto Alegre. It is treated to analyze practical pedagogical literacy teachers in the Public Education. The two chosen public schools have not only been presented positive in the Index of Development of Basic Education (IDEB), as well as relevance of demands in the city. In addition to the analysis of the legal framework, the theoretical framework is based on Emília Ferreiro and Ana Teberosky, (1985) Magda Soares (2017), Paulo Freire (1979), Piaget (1972), Vygotsky (1991), Fernando Becker and Luciana Piccoli and Patrícia Camini (2012).The methodology followed the principles of the qualitative research, adopting the instruments for the collection of data the simple comment, the documentary research and interviews. The participants had been the literacy teachers of the two institutions of education. The analysis of the data if given to the light of the principles of Literal Analysis Discursiva (Moraes and Galiazzi, 2011). The research also approached the legal proposals in the work with the reading and the writing; what the professors adopt the practical pedagogical and the respective epistemologies that underlie to these practical. Another focus of inquiry consisted of presenting a "picture" disclosing the points of evident convergence and divergence in these institutions of public education. The results, we identify that both scenes possess practical - with focus in the planning, the activities and the interventions - that they potentiate and they limit the literacy of the children. Therefore, we indicate the necessity and urgency of valorization and investments in the continuous training of teachers, in order to meet the needs of their continuous qualification.